Hot and sour in the deep ocean. Issue 12 (December 2017) - Sabine, Christopher
Stable layering in the ocean limits the rate that human-derived carbon dioxide can acidify the deep ocean. Now observations show that ocean warming, however, can enhance deep-ocean acidification through increased organic matter decomposition.